A-Si:H/µc-Si:H tandem junction based photocathodes with high open-circuit voltage for efficient hydrogen production. Issue 22 (19th November 2014) - Urbain, Félix; Smirnov, Vladimir; Becker, Jan-Philipp; Rau, Uwe; Finger, Friedhelm; Ziegler, Jürgen; Kaiser, Bernhard; Jaegermann, Wolfram
Abstract